KAPASITAS AEROBIK DAN ANAEROBIK PADA ANAK USIA DINI - Satrio Sakti Rumpoko; Sunjoyo Sunjoyo (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the Anaerobic and Aerobic Capacity of Early Childhood. This research is a descriptive study because it intends to examine and determine as much information as possible from a certain phenomenon and try to give an idea of the anaerobic and aerobic capacity of early childhood. Data collection instruments used the Running-based Anaerobic Sprint Test (RAST) to determine anaerobic capacity and the Multiple Fitness Test to determine aerobic capacity. The study population used was elementary school students. The sample in this study was determined by Purposive Sampling obtained as many as 20 people. Quantitative descriptive statistical analysis techniques. The results of the research can be described as follows: for aerobic capacity, three categories are obtained: the good category is 5 students (25%), the moderate category is 13 students (65%), and the less category there are 2 students (10%), while for anaerobic capacity also obtained three categories namely the good category there are 2 students (10%), the medium category there are 17 students (85%) and the category of less than 1 student (5%).